(untitled) (Heritage, 2025)
This paper deals with the aid in textbooks provided by Serbia to schools in the Ottoman Empire, Montenegro and Austria-Hungary from 1868 (from the beggining of the year and from the foundation of the Comittee for schools and teachers in Old Serbia and Bosnia and Herzegovina in August of 1868) until the end of 1878. Based on archival sources for each individual case, analysis shows that 158 097 copies of various, mainly elementary school texbooks and other literature were sent to numerous schools. Most of them (102 985) were distributed to schools in Old Serbia, the region where Serbia’s interests colided with Bulgarian propaganda. Serbia’s activities in providin aid to schools outside of Serbia was significantlly intensified during this period in comparison with the previous decades (1849-1868). However, the events of The Great Eastern Crisis (1875-1878) reduced this aid to minimum.